Development of cloud-based visual image search platform - Nguyen, Kyle Huu Thanh (2014)
Ecommerce has evolved to be a vibrant industry with hundreds of billions of dollars in revenue each year. The potential has attracted vast number of businesses into the industry and each of them is looking for a competitive advantage that can separate their businesses from the rest.